2005
DOI: 10.1038/nsmb951
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of nicotinic acetylcholine receptor homolog AChBP in complex with an α-conotoxin PnIA variant

Abstract: Conotoxins (Ctx) form a large family of peptide toxins from cone snail venoms that act on a broad spectrum of ion channels and receptors. The subgroup alpha-Ctx specifically and selectively binds to subtypes of nicotinic acetylcholine receptors (nAChRs), which are targets for treatment of several neurological disorders. Here we present the structure at a resolution of 2.4 A of alpha-Ctx PnIA (A10L D14K), a potent blocker of the alpha(7)-nAChR, bound with high affinity to acetylcholine binding protein (AChBP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
422
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(461 citation statements)
references
References 49 publications
34
422
0
5
Order By: Relevance
“…IMI-AcAChBP co-crystal structures [22,38] show that ImI is stabilized in the binding site in the same orientation as PnIA(A10L D14K) albeit through a broader range of interactions [20]. Some of these interactions overlap, but the nature of most of the contacts varies considerably.…”
Section: Achbp-imi Complexmentioning
confidence: 97%
See 2 more Smart Citations
“…IMI-AcAChBP co-crystal structures [22,38] show that ImI is stabilized in the binding site in the same orientation as PnIA(A10L D14K) albeit through a broader range of interactions [20]. Some of these interactions overlap, but the nature of most of the contacts varies considerably.…”
Section: Achbp-imi Complexmentioning
confidence: 97%
“…AChBPs from Lymnaea stagnalis [17], Bulinus truncatus [18] and Aplysia californica [19] share only a 20-24% sequence identity with nAChRs ( Figure 1a) but display a striking structural resemblance with the Torpedo nAChR or mouse α1 nAChR protomer (Figure 1b). Nicotinic ligand binding to these AChBPs was assayed through different methods such as radioligand ( 125 I-αBungarotoxin) displacement, surface plasmon resonance [20][21][22], isothermal titration calorimetry [18] or intrinsic fluorescence quenching [19], and all the AChBPs were found to display a pharmacological profile close to that of the homopentameric α 7 nAChR [18,23].…”
Section: Tools Towards Nachr Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The specific subset of residues with which different ligands interact may overlap but are not necessary identical, as illustrated in the crystal structures of the Aplysia AChBP complexed with ligands [6,7]. Further, our kinetic studies [10,11] suggested that each high affinity binding site is associated with a secondary site lying approximately 15Å away.…”
Section: Discussionmentioning
confidence: 71%
“…The location of these sites has been corroborated by elucidation of the crystal structures of related acetylcholine binding proteins (AChBPs) [e.g. [5][6][7]. There is, however, a body of information to indicate that the binding sites may be more complex than is readily apparent *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%